Instructional Design and Students’ Performance: The Role of the ASSURE Model in Teaching Genetics - Salifu Kasim; Charles Amoah Agyei; Gyamfi Maxwell (Journal of Research in Education and Pedagogy, 2026)
This study investigated the impact of the ASSURE instructional design model on the academic performance of Senior High School (SHS) students in genetics concepts in Ghana. The research was prompted by persistent conceptual challenges faced by biology students in genetics, as documented in prior studies and WAEC Chief Examiners’ Reports. These challenges often result in poor academic outcomes, particularly in topics such as DNA, chromosomes, inheritance, and variation. To address this issue, the study employed a quasi-experimental design using a pre-test/post-test non-equivalent control group. A total of 104 SHS 3 Biology students from four intact classes in the Bawku, Pusiga, and Garu Districts of the Upper East Region were randomly assigned to either an experimental group taught using the ASSURE model or a control group taught using traditional methods. The Genetics Concept Test (GCT), developed by the researchers, was used to assess students’ understanding before and after the intervention. Pre-test results showed the control group outperforming the experimental group. However, post-test analysis using ANCOVA revealed a statistically significant improvement in the experimental group’s performance (M = 23.938, SE = 0.279) compared to the control group (M = 19.483, SE = 0.268; F (1,101) = 121.251, p =.001), with a large effect size (Partial Eta Squared = 0.546). Furthermore, no significant gender differences were found in the experimental group’s post-test scores, suggesting that the ASSURE model supports equitable learning outcomes. The study concludes that the ASSURE instructional design model enhances students’ academic performance in genetics and is gender-sensitive. It recommends its integration into biology instruction to improve conceptual understanding and performance, especially in regions with historically low achievement in genetics.